An overview of various treatment strategies, especially tissue engineering for damaged articular cartilage - Azizeh Rahmani Del Bakhshayesh; Soraya Babaie; Hamid Tayefi Nasrabadi; Nahideh Asadi; Abolfazl Akbarzadeh; Ali Abedelahi (Artificial Cells, Nanomedicine, and Biotechnology)
Many traditional procedures, including surgical methods such as microfracture of subchondral bone and soft tissue transplantation, have been widely used to treat damaged cartilage. However, there is still no definitive cure for cartilage defects. In recent decades, tissue engineering has raised hopes for the repair of defective cartilage. Different approaches are used for cartilage engineering, in which cells, scaffolds, and biological signals or growth factors may be used alone or in combination. Additionally, the imitation of the mechanical properties of the natural cartilage tissue by bioreactors is also helpful in this regard. It should be noted that in the transplantation of engineered cartilage tissue, there are challenges such as poor integration, inflammation and phenotypic instability that may lead to failure of neo-cartilage transplantation. Therefore, a comprehensive understanding of the multiple therapeutic approaches, including surgical procedures, cell-based methods and tissue engineering, should be obtained. The present review article provides this information, along with a variety of factors, including cells, materials, and biological/biomechanical factors required for the engineering of cartilage tissue, as well as the challenges ahead and their solutions.